2017
DOI: 10.25085/rsea.761206
|View full text |Cite
|
Sign up to set email alerts
|

Primer registro de Pseudapanteles dignus (Hymenoptera: Braconidae) como parasitoide de Tuta absoluta (Lepidoptera: Gelechiidae) en el Alto Valle de Río Negro, Argentina

Abstract: The larval endoparasitoid Pseudapanteles dignus (Hymenoptera: Braconidae) is reported for the first time attacking the South American tomato moth Tuta absoluta (Lepidoptera: Gelechiidae) in tomato crops at Alto Valle de Río Negro, being this the most southern report for Argentina. Besides, P. dignus diagnosis and parasitism percentage are briefly commented. Parasitoid. biological control. Pest. Tomato leaf miner. Gelechiidae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
(31 reference statements)
0
2
0
1
Order By: Relevance
“…El proceso agro-productivo de la berenjena para cumplir con su ciclo completo desde la preparación del terreno hasta la recolecta de las diferentes cosechas acuerdo a lo manifestado por los propios agricultores en el departamento durante las visitas de campo y elaboración de las encuestas, deben estar supervisado y controlado permanentemente de plagas que comúnmente se presentan como son: las mosquitas, ácaros, gusanos, grillos, morrocollita y otros, por lo cual se deben controlar y/o erradicar con el uso de insecticidas y plaguicidas, como se determina en las investigaciones de Camacho (2017); Salas Gervassio (2017); Garrido et al (2017); Barraza et al (2017); y Lugo et al (2018).…”
Section: Fuente: Propiaunclassified
“…El proceso agro-productivo de la berenjena para cumplir con su ciclo completo desde la preparación del terreno hasta la recolecta de las diferentes cosechas acuerdo a lo manifestado por los propios agricultores en el departamento durante las visitas de campo y elaboración de las encuestas, deben estar supervisado y controlado permanentemente de plagas que comúnmente se presentan como son: las mosquitas, ácaros, gusanos, grillos, morrocollita y otros, por lo cual se deben controlar y/o erradicar con el uso de insecticidas y plaguicidas, como se determina en las investigaciones de Camacho (2017); Salas Gervassio (2017); Garrido et al (2017); Barraza et al (2017); y Lugo et al (2018).…”
Section: Fuente: Propiaunclassified
“…The scientific knowledge of the insect fauna of the Alto Valle de Río Negro and Neuquén is scarce and strongly associated with pome fruit production for export markets, as illustrated by the following contributions: Hymenoptera (Dapoto & Giganti, 1994;Aquino et al, 2013;Garrido et al, 2017), Hemiptera: Sternorrhyncha (Giganti et al, 2004;Vera et al, 2012), Hemiptera: Auchenorrhyncha (Catalano et al, 2009;Paradell & Dellapé, 2015;D'Hervé et al, 2017); Lepidoptera (Garrido et al, 2007;Dapoto et al, 2010); Neuroptera (Gonzalez et al, 2011), Diptera (Santadino et al, 2015) and Coleoptera (Curculionidae) (del Río et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Control methods for codling moth have mainly been based on the use of broad-spectrum insecticides and, to a lesser extent, more environmentally friendly tools, such as Mating Disruption Technique (Senasa, 2023) and the use of different exotic and native parasitoids (Garrido et al, 2005;Tortosa et al, 2014). Regarding G. legneri as a parasitoid of C. pomonella, Laumann et al (2000a) found a high survival rate, the predominance of females in the offspring and high fecundity, among other characteristics.…”
mentioning
confidence: 99%